Effect of different nutrient management options on growth and yield of basmati rice cultivars - Ashutosh Kumar Rai,; U.P. Shahi,; B.P. Dhyani,; S.P. Singh,; Kamal Khilari,; Adesh Singh,; Anand Singh, (Annals of Agricultural Research, 2023)
An experiment entitled “Effect of different nutrient management options on Growth and yield of basmati rice cultivars’’ was conducted at the Crop Research Centre of Sardar Vallabhbhai Patel University of Agriculture & Technology, Meerut (U.P.) during kharif season of 2020 to 2021. The experiment was conducted in split plot design with 3 basmati rice varieties in main plots and 5 nutrient options in sub plots. The results revealed that the application of integrated nutrient management (50% inorganic + 50 % organic) lead to higher plant height and dry matter accumulation of all basmati varieties at 60 DAT and at harvest. However, at 30 DAT no significant difference in plant height was observed. The application of nutrients as integrated nutrient management-INM as in T3 -(50% inorganic +50% organic) increased plant height of basmati rice significantly by 33.41,1919 and 8.23% at 60 DAT while 33.34,30.33 and 13.15% at harvest over control (T1 ), 5% jeevamruit (T5 ) and 100% organic(T2 ), respectively and it was at par with 100% inorganic. The maximum numberof tillers m-2 (308.29) and dry matter accumulation (788.15 g m-2) at harvest whilecrop growth rateCGR (11.16 gm-2day-1) from 60 DAT to harvest stage were registered with application nutrients as INM (50% inorganic + 50% organic). The use of INM enhanced the SPAD (Subsystem Positioning Aid Device) reading by 18.36, 15.52 and 2.04% at 60 DAT and 35.12, 24.15 and 7.09% at 75 DAT over control, 5% jeevamruit and 100% organics, respectively. The grain, straw, and biological yield of basmati rice due to different nutrient management options differ significantly and under integrated nutrient management grain yield increased by 119.51, 102.20 and 18.84% while straw yield by 64.39, 70.70 and 7.64% over control, 5% jeevamruit and 100% organic, respectively while remain at par with 100% inorganic. It is concluded that integrated nutrient management using 50% inorganic + 50% organic enhanced the productivity of basmati rice cultivars.